Effectiveness of the Ayah ASI Group Education on the Self-efficacy of Pregnant Women in Providing Exclusive Breastfeeding - Saima Putri Siregar; Evi Karota Bukit; Farida Linda Sari Siregar (Universitas STRADA Indonesia, 2024)
The success of exclusive breastfeeding is related to self-efficacy, the mother's belief in her ability to provide exclusive breastfeeding is getting better, and the support ofher husband plays an important role in increasing the mother's self-efficacy. The purpose of this study was to analyze the effectiveness of Ayah ASI group education on pregnant women's self-efficacy in breastfeeding plans. The method used was a quasi experimental non-equivalent with control group pretest-posttest intervention. The sample consisted of 27 respondents in the intervention group at the clinic of Neri midwife clinic and 27 respondents in the control group at Pratama Niar clinic with consecutive sampling technique. The intervention was given in theform of “Ayah ASI” education for three weeks.